The influence of the surface load exerted by a piezoelectric contact sensor on testing results: II. The electrical transients generated by piezoelectric sensor - Radziszewski, L. (Archives of Acoustics, 2003)
The influence of a strong discontinuity wave on its measurement with a apiezoelectric sensor was analysed analytically. The one-dimensional model of the mechanical contact between the ultrasonic sensor and the solid medium was developed. Part I of the paper contained the discussion of the displacement field in the solid, the analysis of electrical transients generated by piezoelectric tranducer are given in this paper. The evaluation was made locally at the front of distortion. It was found that the relative error of PZT transducer’s indication ranges from 26% up to 70%. After a long period of time (depending on the mass M) the influence of surface loading becomes much smaller.